Concomitant administration of seasonal influenza and COVID-19 mRNA vaccines - Teresa Aydillo; Maria Balsera-Manzanero; Amaya Rojo-Fernandez; Alba Escalera; Celia Salamanca-Rivera; Jerónimo Pachón; María Del Mar Muñoz-García; María José Sánchez-Cordero; Javier Sánchez-Céspedes; Adolfo García-Sastre; Elisa Cordero (Emerging Microbes and Infections)
Current clinical guidelines support the concomitant administration of seasonal influenza vaccines and COVID-19 mRNA boosters vaccine. Whether dual vaccination may impact vaccine immunogenicity due to an interference between influenza or SARS-CoV-2 antigens is unknown. We aimed to understand the impact of mRNA COVID-19 vaccines administered concomitantly on the immune response to influenza vaccines. For this, 128 volunteers were vaccinated during the 22-23 influenza season. Three groups of vaccination were assembled: FLU vaccine only (46, 35%) versus volunteers that received the mRNA bivalent COVID-19 vaccines concomitantly to seasonal influenza vaccines, FluCOVID vaccine in the same arm (42, 33%) or different arm (40, 31%), respectively. Sera and whole blood were obtained the day of vaccination, +7, and +28 days after for antibody and T cells response quantification. As expected, side effects were increased in individuals who received the FluCOVID vaccine as compared to FLU vaccine only based on the known reactogenicity of mRNA vaccines. In general, antibody levels were high at 4 weeks post-vaccination and differences were found only for the H3N2 virus when administered in different arms compared to the other groups at day 28 post-vaccination. Additionally, our data showed that subjects that received the FluCOVID vaccine in different arm tended to have better antibody induction than those receiving FLU vaccines for H3N2 virus in the absence of pre-existing immunity. Furthermore, no notable differences in the influenza-specific cellular immune response were found for any of the vaccination groups. Our data supports the concomitant administration of seasonal influenza and mRNA COVID-19 vaccines.